(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The locations in southern Ukraine, ecology and general distribution of the new for Ukraine lichenicolous fungus Pyrenochaeta xanthoriae Diederich as parasite on the corticolous Xanthoria species are provided.